Identification of Tumor Antigens and Immune Landscape in Glioblastoma for mRNA Vaccine Development - Ye, Liguo; Wang, Long; Yang, Ji’an; Hu, Ping; Zhang, Chunyu; Tong, Shi’ao; Liu, Zhennan; Tian, Daofeng (Frontiers in Genetics, 2021)
Background: Clinical benefits from standard therapies against glioblastoma (GBM) are limited in part due to intrinsic radio- and chemo-resistance. As an essential part of tumor immunotherapy for adjunct, therapeutic tumor vaccines have been effective against multiple solid cancers, while their efficacy against GBM remains undefined. Therefore, this study aims to find the possible tumor antigens of GBM and identify the suitable population for cancer vaccination through immunophenotyping. Method: The genomic and responding clinical data of 169 GBM samples and 5 normal brain samples were obtained from TCGA, the mRNA_seq data of 940 normal brain tissue were downloaded from GTEx. Potential GBM mRNA antigens were screened out by differential expression, copy number variant (CNV), and mutation analysis. K-M survival and Cox analysis were carried out to investigate the prognostic association of potential tumor antigens. TIMER was used to explore the association between the antigens and tumor immune infiltrating cells. Immunophenotyping of 169 samples was performed through consensus clustering based on the abundance of 22 kinds of immune cells."". The characteristics of tumor immune microenvironment in each cluster were explored through single-sample gene set enrichment analysis based on 29 kinds of immune-related hallmarks and pathways. Weighted gene co-expression network analysis (WGCNA) was performed to cluster genes related to immune subtypes. Finally, pathway enrichment analyses were performed to annotate the potential function of modules screened through WGCNA. Results: Two potential tumor antigens selected were significantly positively associated with the antigen-presenting immune cells (APCs) in GBM. Furthermore, the expression of antigens was verified at the protein level by Immunohistochemistry. Two robust immune subtypes, IS1 and IS2, representing immune status "immune inhibition" and "immune inflamed" respectively had distinct clinical outcomes in GBM. Conclusion: ARPC1B and HK3 were potential mRNA antigens for developing GBM mRNA vaccination, and the patients in IS2 were considered the most suitable population for vaccination in GBM.